Effect of life course factors on dental fear among adult dental patients attending out-reach clinics in a rural area of Southern India - Valerie G D'Costa; Deepak K Singhal; Shashidhar Acharya (Wolters Kluwer Medknow Publications, 2022)
Objectives: The aim of the study was to assess the effect of life course factors on dental fear among adult dental patients attending out-reach clinics in a rural area of South India. The objectives were to measure dental fear and changes in socio-economic status during the life course among the study population and to know whether social mobility reduced/increased dental fear. Methods: Dental fear scale and life course data were collected from 403 respondents. The improvement status of individual life course criteria was categorised into "less/minimal", "stable", or "upwardly mobile". Results: The odds of dental fear in the group showing less or minimal upward social mobility was two times that of the stable group [p = 0.022; 95% confidence interval (C.I): 1.104-3.598], whereas the odds of dental fear in the group showing more or good upward social mobility were 4.5 times that of the stable group [p = 0.001; 95% C.I: 1.928-10.515] when adjusted for covariates, that is, participant age, gender, and education and past history of dental avoidance. Conclusion: Social mobility was found to be a risk indicator for dental fear. Dental services may have been affected even with increased standards of living because of psychological factors such as dental fear.